Pengaruh Kombinasi Latihan Progressive Muscle Relaxation (PMR) dan Pijat Punggung Terhadap Tekanan Darah pada Penderita Hipertensi di Wilayah RW 001 Sarua Indah Ciputat Tangerang Selatan Tahun 2022 - Hendra Irawan; Indri Sarwili; Elvie Tresya (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
This study aims to determine the effect of a combination of Progressive Muscle Relaxation (PMR) exercises and back massage on blood pressure in hypertension sufferers in the RW001 Sarua Indah Ciputat area, South Tangerang. This research uses a descriptive study type of research with a quantitative approach. The appropriate method for this research is the pre-experimental research method. Design Pre-experimental design is a design that includes only one group or class that is given pre- and post-tests (Sugiyono, 2014). This research design only uses a single group, so it does not require a control group. Before being given treatment, the experimental group first underwent a pretest, followed by action (intervention), namely using a combination of Progressive Muscle Relaxation and Back Massage exercises, then continued with giving a posttest.